Could remnant-like particle cholesterol become a risk factor in diabetic menopausal women with coronary artery disease? A cross-sectional study of single academic center in China - Xunxun Feng; Qianyun Guo; Shu Zhou; Tienan Sun; Yuyang Liu; Zhiming Zhou; Yujie Zhou (Lipids in Health and Disease, 2020)
Abstract Background and aims It has been confirmed that remnant-like particle cholesterol (RLP-C) mediates the progression of coronary artery disease (CAD). Currently there is limited information on RLP-C in menopausal women. With the special status of diabetes mellitus (DM) combined with the special body changes of the menopausal women, the RLP-C is particularly important when studying the changes that occurred in response to CAD and its associated risk factors. This study discussed whether RLP-C could be an independent risk factor for menopausal women with CAD and DM. Methods The cohort consisted of 4753 menopausal women who had undergone coronary angiography. Subjects were separated into CAD and non-CAD groups, and univariate and multivariate logistic regression analysis of CAD risk factors were performed. All patients with a history of DM were divided into DM subgroups. Then, the univariate and multivariate logistic regression analysis of the risk factors of CAD and the comparison among age groups in the DM subgroup were performed. After age stratification of the DM group, the Kruskal-Wallis test was used to analyze the differences of various lipid indexes among age groups. Results The multivariate logistic regression showed that RLP-C was an independent risk factor for CAD in menopausal women (OR 1.232, 95%CI 1.070–1.419). In the DM subgroup, it was also found that RLP-C was an independent risk factor for CAD (OR 1.366, 95%CI 1.043–1.791). Kruskal-Wallis test analysis found that RLP-C had no significant difference among three groups (P > 0.05). Conclusions RLP-C was proved to be an independent risk factor for menopausal women with CAD and DM.